Avaliação de parâmetros isocinéticos da articulação do ombro de atletas de basquete em cadeira de rodas : há correlação com a classificação funcional? - Oliveira, Hudson Renato de Paula (2017)
Wheelchair basketball (WB) is the most popular paralimpic sports. Among the benefits of its practice, we can mention an improvement in function and physical capacity, strength and quality of life in general. To evaluate isokinetic parameters (IP) of the shoulder joint in WB athletes and to correlate with sport class (SC). METHODS: This was a cross-sectional study, a convenience sample of 22 WB athletes (12 men and 10 women) with different types of injuries and affections. For the isokinetic evaluation, an electromechanical dynamometer is used. A joint evaluated for the shoulder on the dominant (D) and non-dominant (ND) sides at angular velocities of 60 and 240 ° / s-1 in internal rotation (IR) and external rotation (ER). A SC was determined according to the parameter (functional tests, medical evaluations and evaluations in game situations), International Paralympic Committee (IPC) and international federation of wheelchair basketball (IWBF). RESULTS: Our main findings, which are a strong association at 60 ° / s -1 and at 240 ° / sec -1. (R = 0.5) and in the relative variable work fatigue -D-IR (r = -0.5). However, at the velocity of 240 ° / s -1 for a time to peak torque -D-ER a moderate negative association. CONCLUSION: The SC of the WB athletes did not correlate expressively with IP of the shoulder joint. However, in view of a wide variability of factors (type of injury, etiology, level of injury, time of injury, gender etc.), an interpretation of our findings needs to be made with caution. Future studies, performed on more homogeneous samples to produce more satisfactory results.